Dental status of persons engaged in sports swimming - Y. A. Grebennikov; N. D. Golberg (National Electronic Information Consortium (NEICON), 2020)
To date, information on the problem is contradictory and ambiguous. It is difficult to trace cause - effect relationships between the condition of hard dental tissues, oral fluid, the dental status of swimmers, and the characteristics of the water environment of training pools. The article presents an analysis and systematization of literature on the dental condition in swimming athletes, as well as formulates modern ideas on the subject and highlights topics for further research.